Boiling effect in crater development on magnesium surface induced by laser melting - Guan, Yingchun (2016)
This paper demonstrated that micron-craters could be fabricated on both magnesium and Mg alloy surfaces by nanosecond pulsed laser processing. Experimental results revealed that the craters with broad distribution of dimension occurred after laser melting. Morphological difference at the irradiated surface between Mg and Mg alloy indicated that thermal properties, alloying elements and microstructure of irradiated materials were key factors responsible for crater formation. It was proposed that the craters were formed by combined effect of explosive volume boiling and generation of cavitation bubbles during laser melting. Thermal effect of nanosecond pulsed laser processing on Mg and Mg alloy as well as progressive formation of laser-induced crater was further discussed. Such phenomenon extended potential applications of Mg materials, which offered the potential for developing new types of Mg-based biomedical devices.